2009
DOI: 10.1371/journal.pone.0004782
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence for Cell Membrane Amelioration in Children with Cystic Fibrosis by 5-MTHF and Vitamin B12 Supplementation: A Single Arm Trial

Abstract: BackgroundCystic fibrosis (CF) is one of the most common fatal autosomal recessive disorders in the Caucasian population caused by mutations of gene for the cystic fibrosis transmembrane conductance regulator (CFTR). New experimental therapeutic strategies for CF propose a diet supplementation to affect the plasma membrane fluidity and to modulate amplified inflammatory response. The objective of this study was to evaluate the efficacy of 5-methyltetrahydrofolate (5-MTHF) and vitamin B12 supplementation for am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Reduced ratios of S-adenosylmethionine to S-adenosylhomocysteine and of PC to phosphatidylethanolamine in plasma, and phospholipid malabsorption have also been reported in CF children [36]. These altered values are reversed by PC treatment [36] and also by administration of 5-methyltetrahydrofolate [37]. Another enzyme involved in PC synthesis is CTP∶phosphocholine cytidylyltransferase.…”
Section: Discussionmentioning
confidence: 96%
“…Reduced ratios of S-adenosylmethionine to S-adenosylhomocysteine and of PC to phosphatidylethanolamine in plasma, and phospholipid malabsorption have also been reported in CF children [36]. These altered values are reversed by PC treatment [36] and also by administration of 5-methyltetrahydrofolate [37]. Another enzyme involved in PC synthesis is CTP∶phosphocholine cytidylyltransferase.…”
Section: Discussionmentioning
confidence: 96%
“…It is unclear whether there are clinical benefits of B 12 intake beyond that to sustain a normal B 12 status. Scambi et al (33) reported improvements in phospholipid docosahexaenoic acid (DHA) status in young children with CF with daily 5‐methyltetrahydrofolate (7.5 mg) and B 12 (0.5 mg) supplementation in a 24‐week intervention. The phospholipid DHA improvement was thought to be a result of the interaction of folate, B 12 , phospholipid DHA, and 1‐methyl metabolic pathway (33).…”
Section: Discussionmentioning
confidence: 99%
“…14 It is noteworthy then that Cbl is an active superoxide scavenger; 15,16 reduced forms of Cbl are required for its coenzyme activity; 2 cellular uptake of Cbl may be impaired by oxidative byproducts; 17 and functional Cbl deficiency occurs after exercise and in many other pro-oxidant disorders. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Significantly, diabetes and folate excess, both of which are associated with increased oxidative stress, have been linked to functional Cbl deficiency in the elderly but not in younger individuals. 10,18,21 These observations suggest that functional Cbl deficiency may be associated with oxidative stress and that this relationship may be particularly prevalent in the elderly.…”
Section: Introductionmentioning
confidence: 99%